2007
DOI: 10.1002/ptr.2145
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and antiinflammatory activity of Cyclamen repandum S. et S.

Abstract: According to folk medicine some species belonging to the genus Cyclamen were used for their biological activities. Early investigation of the different species of the genus resulted in the isolation of triterpenic saponins. No phytochemical and biological data are available on C. repandum. As part of a series of phytochemical investigations for bioactive compounds from medicinal plants, Cyclamen repandum S. et S. was investigated. The present study sought to find the antiinflammatory and antinociceptive activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The genus Cyclamen L. (Primulaceae) is represented by around 20 wild and cultivated species (Speroni et al, 2007). Three of them, Cyclamen persicum Mill, Cyclamen coum Mill, and Cyclamen libanoticum Hildebr, can be found in Lebanese soils, but only C. libanoticum is endemic of the Lebanese flora.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Cyclamen L. (Primulaceae) is represented by around 20 wild and cultivated species (Speroni et al, 2007). Three of them, Cyclamen persicum Mill, Cyclamen coum Mill, and Cyclamen libanoticum Hildebr, can be found in Lebanese soils, but only C. libanoticum is endemic of the Lebanese flora.…”
Section: Introductionmentioning
confidence: 99%
“…Three of them, Cyclamen persicum Mill, Cyclamen coum Mill, and Cyclamen libanoticum Hildebr, can be found in Lebanese soils, but only C. libanoticum is endemic of the Lebanese flora. Cyclamen tubers have been used in the folk medicine for their sedative, purgative, antihelmintic, laxative, and abortive properties (Speroni et al, 2007). Different extracts of Cyclamen tubers were shown to possess cytotoxic, antimicrobial, spermicidal, analgesic, and anti-inflammatory activities (Ç aliş et al, 1997;Dall'Acqua et al, 2010;Kupchan et al, 1967;Mahasneh & El-Oqlah, 1999;Primorac et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed the effi cacy of compound 9 in different antinociceptive responses generated by a chemical noxious stimulus produced by acetic acid injections or by a thermal noxious stimulus in the hot plate tests. The anti-infl ammatory and antinociceptive activities of compound 9 may be attributed to the oleane-type triterpene (Speroni et al, 2007).…”
Section: Biological Resultsmentioning
confidence: 99%
“…6,9 In vi vo si de ef fects are lo cal and tem po rary be ca u se the pro duct is not ab sor bed or enters the blo ods tre am. [10][11][12] In this study, in vit ro cyto to xic ef fect of a new com mer ci al plant ex tract (Cycla men eu ro pa e um) (Na sod ren na sal spray) was in ves ti ga ted in L929 fib rob last cul tu re. The in vit ro to xic ef fect of the drug se e med to be do se de pen dent and ir re ver sible.…”
Section: Discussionmentioning
confidence: 99%